BSCL: Blockchain-Oriented SDN Controlled cloud based Li-Fi communication architecture for smart city network - Khan, Fazeel Ahmed; Ibrahim, Adamu Abubakar; Marwan, Mahmoud; Al-Khasawneh, Mahmoud Ahmad; Alarood, Ala Abdulsalam (Science Publishing Corporation Inc, 2018)
The Internet of Things (IoT) smart city initiative has transformed technology spectrum into its new era of development. The increasing amount of data generated by millions of IoT devices and the rapid flow of data across distributed IoT devices are transmitting to remotely located cloud infrastructure over the Internet. Unfortunately, these large amounts of data and its flow based on the traditional energy-intensive network infrastructure is neither efficient nor substantially scalable. It is essential to design a comprehensive network infra-structure to handle large amount of high-speed data-processing in an IoT spectrum. Apparently, Blockchain and Software-Defined Net-working (SDN) approaches can leveraged the scalability of the environment for IoT spectrum. In addition, the emergence of distributed cloud technology and Li-Fi spectrum can transform the capability of data-processing for IoT devices. The challenge lies in efficiently blend the integration of Li-Fi, Blockchain, SDN and Cloud technologies for IoT environment. To address this challenge, we design a multiaccess communication modulation model for efficient optimization of distributed network with an SDN based controller and inte-gration of robust cloud infrastructure for high-speed data-processing. The proposed model is based on Li-Fi communication architecture which significantly reduced in the utilization of energy for managing large-scale infrastructure. We performed simulation and analysis across multiple dimensions to evaluate the performance and effectiveness of our proposed model. The evaluated output shows that our model significantly improved the overall performance and efficiency of the communication infrastructure as compared with other ultra-modern models.